2020
DOI: 10.1002/ange.202000652
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective [4+2]‐Cycloaddition with Chiral Alkenylboranes

Abstract: A method for the stereoselective [4+2]‐cycloaddition of alkenylboranes and dienes is presented. This transformation was accomplished through the introduction of a new strategy that involves the use of chiral N‐protonated alkenyl oxazaborolidines as dieneophiles. The reaction leads to the formation of products that can be readily derivatized to more complex structural motifs through stereospecific transformations of the C−B bond such as oxidation and homologation. Detailed computation evaluation of the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…21,29,33 This is in a good agreement with the fact that the aromaticplanar Bdan group is less bulky than the Bpin group. 13,27,32,42 Therefore, it would appear that the diastereoselectivity in this case is driven primarily by sterics.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…21,29,33 This is in a good agreement with the fact that the aromaticplanar Bdan group is less bulky than the Bpin group. 13,27,32,42 Therefore, it would appear that the diastereoselectivity in this case is driven primarily by sterics.…”
Section: Resultsmentioning
confidence: 92%
“…We posited that an efficient way to prepare gem-diboryl-norbornene structural motifs 4 would be through a [4+2] cycloaddition reaction of gem-diborylalkenes 2 with cyclopentadiene-CP 3. Although the [4+2] cycloaddition reactions of vinylboranates, 26 e.g., 1, are well documented in the literature (Figure 2A), [27][28][29][30] to the best of our knowledge, the use of gem-diboryllkenes (2) in these types of reactions is rare, despite the potential to provide new and efficient strategies to efficiently construct complex molecules (Figure 2B). 28,30 Recently, we reported a photoredox-mediated reaction of gemdiborylalkenes 31 and showed that gemdiboryalkenes (2) are more electron deficient compared to vinyl-boron 1; 31 hence, 2 should serve as a suitable dienophile for this type of cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author engages Corey's activated chiral oxazaborolidine based chiral auxilary [15] to maintain the rigid structure. They developed a stereoselective [4+2]‐cycloaddition protocol accomplishing N ‐protonated alkenyl oxazaborolidines as a dienophile [46] . They cleverly designed the 5 : 5 fused ring system, where the substituent on the concave face energetically disfavors the approach of diene.…”
Section: Asymmetric [4+2] Cycloaddition Using Organoboron Compoundmentioning
confidence: 99%
“…They developed a stereoselective [4 + 2]-cycloaddition protocol accomplishing Nprotonated alkenyl oxazaborolidines as a dienophile. [46] They cleverly designed the 5 : 5 fused ring system, where the substituent on the concave face energetically disfavors the approach of diene. The author utilized diphenylprolinol as the chiral auxiliary, which also generated a chiral alkenyl oxazabor- olidine in situ and later on converted into a highly reactive dienophile via Lewis acid or Brønsted acid activation.…”
Section: Asymmetric Diels-alder Reaction Using Chiral Auxiliarymentioning
confidence: 99%